2020
DOI: 10.1155/2020/1437126
|View full text |Cite
|
Sign up to set email alerts
|

Development and Experimental Verification of an Ergonomic Backpack

Abstract: Carrying a heavy school backpack has extensively been reported as a prime cause of children’s body strain. It is suggested that the load should not exceed 10 percent of the child’s body weight; however, ensuring this requires continuous monitoring. The study explores how ergonomically designed school backpack based on the user anthropometric data (n=280) and ergonomic parameters help reduce force concentration on shoulders and back. It provides a validation process of the developed prototype by experimental ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…In one research done by Layuk et al (2020) revealed that among the reported discomforts related to backpack use, Low Back Pain (LBP) was most commonly mentioned issue, with 33.2% of respondents experiencing it. Subsequently, muscle soreness was reported by 24.4% of respondents, followed by neck pain at 23.5%, upper back pain (UBP) at 10.5%, arm pain at 5.8%, tingling sensations at 4%, and leg pain at 3.6% (20) . The back pack design in our study prevents overloading the spine with excessive weight, which is a common cause of back pain in school children by its force transmission of weight distribution anteriorly.…”
Section: Resultsmentioning
confidence: 99%
“…In one research done by Layuk et al (2020) revealed that among the reported discomforts related to backpack use, Low Back Pain (LBP) was most commonly mentioned issue, with 33.2% of respondents experiencing it. Subsequently, muscle soreness was reported by 24.4% of respondents, followed by neck pain at 23.5%, upper back pain (UBP) at 10.5%, arm pain at 5.8%, tingling sensations at 4%, and leg pain at 3.6% (20) . The back pack design in our study prevents overloading the spine with excessive weight, which is a common cause of back pain in school children by its force transmission of weight distribution anteriorly.…”
Section: Resultsmentioning
confidence: 99%